2018
DOI: 10.1111/jbg.12335
|View full text |Cite
|
Sign up to set email alerts
|

Accurate genomic predictions for BCWD resistance in rainbow trout are achieved using low‐density SNP panels: Evidence that long‐range LD is a major contributing factor

Abstract: Previously accurate genomic predictions for Bacterial cold water disease (BCWD) resistance in rainbow trout were obtained using a medium-density single nucleotide polymorphism (SNP) array. Here, the impact of lower-density SNP panels on the accuracy of genomic predictions was investigated in a commercial rainbow trout breeding population. Using progeny performance data, the accuracy of genomic breeding values (GEBV) using 35K, 10K, 3K, 1K, 500, 300 and 200 SNP panels as well as a panel with 70 quantitative tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
114
4
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(138 citation statements)
references
References 26 publications
17
114
4
3
Order By: Relevance
“…Thus, the minimum number of markers for a high power genomic analysis should be at 351 least,8,300,6,700 and 4,200 for POP A,POP B and POP C,respectively;numbers 352 slightly lower than those suggested by Vallejo et al (2018) and Barria et al (2018a) for also depend on other factors such as the number of individuals genotyped and 356 phenotyped in the training population and the heritability and number of loci affecting 357 the trait (Daetwyler et al, 2008;Goddard, 2009). In preliminary studies of genomic 358 prediction for Nile tilapia, we found high accuracies of GEBV (results not show) for 359 complex traits, using a similar number of markers but a smaller number of animals 360 suggested by Meuwissen (2009).…”
Section: Philippines 300mentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, the minimum number of markers for a high power genomic analysis should be at 351 least,8,300,6,700 and 4,200 for POP A,POP B and POP C,respectively;numbers 352 slightly lower than those suggested by Vallejo et al (2018) and Barria et al (2018a) for also depend on other factors such as the number of individuals genotyped and 356 phenotyped in the training population and the heritability and number of loci affecting 357 the trait (Daetwyler et al, 2008;Goddard, 2009). In preliminary studies of genomic 358 prediction for Nile tilapia, we found high accuracies of GEBV (results not show) for 359 complex traits, using a similar number of markers but a smaller number of animals 360 suggested by Meuwissen (2009).…”
Section: Philippines 300mentioning
confidence: 93%
“…The LD estimation for POP A resulted in slightly different values at 317 small distance compared to POP B and POP C, whereas at large distance the differences 318 were more evident for POP C (Figure 4). These results were reflected in smaller Ne of 319 many generations ago for POP A and smaller Ne in the recent past for POP C (Figure 320 smaller Ne was found for for rainbow trout (Vallejo et al, 2018) and Atlantic salmon 330 from North America, Europe (Barria et al, 2018c) and Tasmania (Kijas et al, 2016). 331…”
Section: Philippines 300mentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, a high-density linkage map containing 20 000 SNPs has recently been created and aligned with the physical reference genome assembly (Zhang et al 2012;Gutierrez et al 2018a). Using such arrays, several studies have demonstrated that genomic selection for aquaculture species results in improved accuracy compared with traditional pedigree-based approaches; for example in Atlantic salmon (Robledo et al 2018), coho salmon (Barr ıa et al 2018), rainbow trout (Vallejo et al 2018), common carp (Palaiokostas et al 2018b) and Pacific oyster (Gutierrez et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…In outbred natural populations of rainbow trout, LD typically spans thousands of bases (<10 kb, Chen, Farrell, Matala, Hoffman, & Narum, ), and average LD in natural European eel ( Anguilla Anguilla ) populations suggest a similar distance, with LD = 10–20 kb (Pujolar et al, ). Genome‐wide LD analysis on an inbred hatchery line of rainbow trout revealed much stronger LD ( r 2 ≥ 0.25) spanning on average over 1 Mb across the genome (Vallejo et al, ). The close mapping distance of the two significant markers observed here presents a target for future research.…”
Section: Discussionmentioning
confidence: 99%